Household air pollution from solid fuel use and cardiorespiratory disease in the China Kadoorie Biobank Cohort Study - Chan, K (2018)
Background: Worldwide >2.7 billion individuals, including 450 million in China, are regularly exposed to household air pollution (HAP) from solid fuel use. HAP may lead to increased risk of cardiorespiratory disease, but epidemiological evidence is still limited and highly heterogeneous. Moreover, there is little data about the potential mitigation effects of ventilation and clean fuel adoption. Methods: The prospective China Kadoorie Biobank (CKB) enrolled 512,891 adults from five rural and five urban areas of China in 2004-2008. After ~9 years of follow-up, there were 11,464 cardiovascular deaths, including 3,982 from ischaemic heart disease (IHD) and 5,338 from stroke among 463,222 participants without prior history of CVD or cancer at baseline. For respiratory disease, the main analyses were further restricted to never-smokers who had no prior history of respiratory disease to minimise not only reverse causality but also confounding by smoking, one of the strongest risk factors of respiratory disease. Among 289,945 never-smokers, there were 23,078 incident major respiratory diseases, including 12,346 chronic lower respiratory disease (CLRD; with 5,093 chronic obstructive pulmonary disease [COPD]), 8,422 acute lower respiratory infection (ALRI), 3,586 acute upper respiratory infection (AURI) and 793 respiratory deaths. Cox regression was used to estimate adjusted hazard ratios (HRs) and floating absolute risk method was used to calculate group-specific 95% confidence intervals (CIs) of each disease endpoint associated with use of different fuels for cooking and heating separately. This abstract presents the main findings on solid fuel use for cooking. Results: In CKB, the mean age (SD) was 51.6 (10.7) years and 59% were women. Solid fuel use for both cooking and heating had declined over time, particularly in urban areas. At baseline, 85% and 12% of rural and urban participants, respectively, reported using solid fuels for cooking throughout their three most-recent residences (average ~40 years). Compared to long-term clean fuel use, solid fuel use for cooking was associated with increased cardiovascular mortality (HR=1.14, group-specific 95%CI 1.09-1.20), which was mainly driven by stroke (1.27, 1.19-1.35) rather than IHD (0.95, 0.87-1.04). For stroke types, the HRs were somewhat greater for ischaemic stroke (1,200 cases; 1.41, 1.22-1.63) than for intracerebral haemorrhage (3,814 cases; 1.27, 1.18-1.36). Participants who switched from solid to clean fuels had no excess risk of cardiovascular death (0.99, 0.93-1.07), but prolonged use of ventilated cookstoves with solid fuels did not alter the association. The association of solid fuel use for cooking with cardiovascular death was consistent across most population subgroups, but persisted in never- (1.33, 1.15-1.53) but not in ever- (1.00, 0.88-1.14) smokers (Pheterogeneity=0.0037). Among never-smokers, solid fuel use for cooking was associated with increased risk of different types of respiratory diseases, with adjusted HRs of 1.47 (1.42-1.53) for CLRD, 1.10 (1.03-1.17) for COPD, 1.18 (1.11-1.25) for ALRI, 1.59 (1.48-1.71) for AURI and 1.53 (1.26-1.85) for respiratory death. Participants who switched from solid to clean fuels had smaller HRs for all respiratory outcomes examined, compared with long-term solid fuels users (e.g. CLRD: 1.20, 1.15-1.26; ALRI: 1.08, 1.02-1.13). Compared with those without using ventilated cookstoves, prolonged use of ventilated cookstoves with solid fuels had smaller HRs for CLRD (1.35, 1.32-1.39 versus 1.45, 1.40-1.51) and AURI (1.52, 1.42-1.63 versus 1.81, 1.66-1.96). Conclusions: In this Chinese population, long-term solid fuel use for cooking was associated with significantly elevated risks of a range of cardiorespiratory disease outcomes, some of which may be mitigated by adopting clean fuels or, to a lesser extent, use of ventilated cookstoves.